(untitled) (Central Asian Journal of Medical Sciences, 2024)
Objective: This study aimed to assess maternal outcomes in women with Gestational Diabetes Mellitus. Method: A multicenter, age, and pre-pregnancy body mass index-matched prospective cohort study was conducted in five maternity hospitals across Ulaanbaatar, Mongolia, between February and April 2022. All participants (24-28 weeks pregnant) underwent an oral glucose tolerance test (OGTT; 75 g, oral glucose, capillary), and the results were considered as GDM (ADA, 2022). The GDM and non-GDM groups were followed from pregnancy to delivery. Maternal and neonatal delivery outcome data were extracted from the clinical records of five maternity hospitals. Results: The mean age and pre-pregnancy BMI were 35.05±3.8 years and 26.21±3.7 kg/m2, respectively. According to the univariate analysis, women with gestational diabetes had higher rates of pregnancy-induced hypertension, cesarean delivery, and labor induction than the non-GDM group. On the multivariate analysis, the risk of undergoing cesarean delivery and developing pregnancy-induced hypertension were 2.8 (aOR=2.83 CI=1.07-7.47) and 6.9 (aOR=6.91 CI=1.35-35.23) times higher, respectively, in the case group compared to the non-GDM group. Conclusion: Women with GDM had more complications during pregnancy and delivery than those without.